Sosialisasi Etika Berwirausaha Islami di Era Covid-19:: Pengabdian Masyarakat di Dusun Dibal Tengah, Dibal, Ngemplak, Boyolali - Andi Mardian; Zaidah Nur Rosidah; Siti Rokhaniyah (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2023)
The Covid-19 pandemic has an impact on all aspects of people's lives, including the economic aspect. Among the effects of the Covid-19 Pandemic felt by most people in terms of the economy are; income decreased until they were forced to lose their jobs. In difficult conditions like this, not a few people are trying to make ends meet without paying attention to ethics. This is due to the pressure of difficult circumstances and the absence of an understanding of the importance of applying Islamic ethics in work and/or entrepreneurship. The impact of the Covid-19 pandemic was also felt by the majority of residents of Central Dibal, Dibal Village, Ngemplak District, Boyolali Regency. In order to anticipate various unethical actions in work and entrepreneurship, it is necessary to socialize about Islamic entrepreneurship ethics. The aim is to educate the public about the importance of ethical principles of Islamic entrepreneurship, especially in unfavorable circumstances as a result of the Covid-19 Pandemic. This socialization activity was carried out using the lecture method from the resource persons and continued with questions and answers and discussions. Residents of Central Dibal feel a number of benefits from the implementation of this community service activity. Among the benefits obtained are; (1) people get comprehensive knowledge about ethics in doing business or entrepreneurship in an Islamic way; (2) the public is aware of the importance of understanding entrepreneurship in an Islamic way in order to avoid sustenance that is not blessed; (3) the community feels the importance of applying Islamic entrepreneurship ethics in various conditions, even though the economic conditions are difficult in the midst of the Covid-19 Pandemic that hit. Keywords: Islamic entrepreneurship ethics; Covid-19 pandemic; socialization